Price, Trade Volume and Return in the Ethereum Market: An ARDL Model - Liaqat, Osama; Nizam, Kehkashan; Alvi, Jahanzaib; Jehandad, Arbab Muhammad (iRASD Journal of Economics, 2023)
This research analyzes the price-setting behaviors of Ethereum, a digital currency and alternative payment system that has gained significant attention from investors. By employing symmetric and asymmetric causality tests, the study identifies the link between Ethereum's return, price, and volume from August 7, 2015, to November 30, 2020. The data obtained from CoinMarketCap.com consists of 1,940 observations suitable for analysis. The research employs ARDL, ARDL bound tests, and VECM to achieve its objectives. The findings indicate a significant and positive association between Ethereum's return, price, and trading volume in the short and long run. This suggests that as Ethereum's price and trading volume increase, it attracts more investors and leads to higher returns.